Turning Daily Time Pressure into a Creative Day: The Interactionist Roles of Employee Neuroticism and Time Pressure Dispersion. Issue 3 (25th January 2019) - Bormann, Kai C.
Abstract : The purpose of this study was to explore under which circumstances daily time pressure is positively related to daily creativity. Building on resource allocation and uncertainty theory, it is argued that highly neurotic individuals' creativity, relative to their emotionally stable counterparts, is more strongly enhanced by daily time pressure. This effect, however, should only emerge in instances of highly consistent daily time pressure over time. To test this model, a diary study was conducted spanning over five subsequent working days. The sample consisted of 250 individuals with 1, 156 daily measurement points. As expected, neuroticism and dispersion of time pressure over time jointly moderated the relationship between daily time pressure and daily creativity. The relationship was positive and significant only when individuals ranked high in neuroticism and dispersion of time pressure was low. The results of this study suggest that under certain circumstances, neurotic individuals are able to realise more gains from increased time pressure compared to their emotionally stable counterparts.